Contradictions in digital health engagement: An activity tracker's ambiguous influence on vulnerable young adults' engagement in own health. (May 2018) - Kanstrup, Anne Marie; Bertelsen, Pernille; Jensen, Martin B
Objective: Activity trackers are designed to support individuals in monitoring and increasing their physical activity. The use of activity trackers among individuals diagnosed with depression and anxiety has not yet been examined. This pilot study investigates how this target group engages with an activity tracker during a 10-week health intervention aimed to increase their physical activity level and improve their physical and mental health. Methods: Two groups of 11 young adults (aged 18–29 years) diagnosed with depression or anxiety participated in the digital health intervention. The study used mixed methods to investigate the research question. Quantitative health data were used to assess the intervention's influence on the participants' health and qualitative data provided insights into the participants' digital health experience. Results: The study demonstrated an ambiguous influence from the use of an activity tracker with positive physical and mental health results, but a fading and even negative digital health engagement and counterproductive competition. Conclusions: The ambiguous results identify a need for (1) developing strategies for health professionals to provide supervised use of activity trackers and support the target groups' abilities to convert health information about physical activity into positive health strategies, and (2) designing alternatives for health promoting IT targeted users who face challenges and need motivation beyond self-tracking and competition.